Translation and interpreting self-efficacy: a review of published measures - Abdel Latif, Muhammad M. M.; Alhamad, Majed M. (Frontiers in Psychology, 2025)
An important area of research in translation and interpreting assessment focuses on measuring translators’ and interpreters’ self-ability beliefs, normally characterized by two main constructs: self-efficacy and self-concept. Self-ability beliefs have a potential relationship with translators’ and interpreters’ task performance and perseverance. While several self-efficacy measures for translators and interpreters exist, no self-concept scales appear to have been published to date. In this article, we review seven published scales assessing translation and interpreting self-efficacy (four translation and three interpreting measures). In our review, we discuss the extent to which the items of the scales represent the constructs being assessed, as well as the translation or interpreting competences they cover. The review indicated that the seven self-efficacy measures focus on only a limited number of translation and interpreting competences. In addition, their items assess the target competences only partially. A few items related to self-concept were also found in the three reviewed interpreting self-efficacy measures. It is concluded that advancing translation and interpreting self-efficacy measurements requires adopting different orientations. The article highlights the self-efficacy measurement gaps that should be addressed in future translation and interpreting research.